Pengembangan Media Ajar Augmented Reality Card Simulasi Pengenalan Bangun Ruang Berbasis Assemblr Edu untuk Meningkatkan Minat dan Hasil Belajar Siswa - Sabila, Siti Zahra; Azmi, Nadya; Hadriana, Syalaisha Dwi; Aini, Putri Nur; Siregar, Sutan Surya Darpan; Siregar, Nurhasanah (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aims to develop Augmented Reality (AR) learning media based on Assemblr Edu for the topic of flat-faced geometric shapes and to determine its feasibility, practicality, and impact on students' interest and learning outcomes. The research method used is Research and Development (R&D) with the 4D development model, which includes Define, Design, Develop, and Disseminate. The subjects of the study were eighth-grade students at SMP Swasta Cerdas Murni during the 2024/2025 academic year. Research instruments consisted of expert validation sheets, learning interest questionnaires, teacher response questionnaires, and learning outcome tests (pretest and posttest). The results of expert validation on the material obtained an average score of 84%, and media expert validation scored 95%, both categorized as "Very Valid," while teachers' responses to the learning media scored 84%, categorized as "Very Practical”. Based on the data analysis results, there was an increase in the average student learning outcomes from 59.11 in the pretest to 83.75 in the posttest, with a significance value of 0.000 < 0.05, indicating a significant improvement in learning outcomes. In addition, students' learning interest also increased from an average score of 43.75 to 62.71, with a significance value of 0.000 < 0.05, indicating a significant increase as well. Therefore, the Assemblr Edu-based Augmented Reality learning media is deemed feasible, practical, and effective in enhancing students' interest and learning outcomes in the material of flat-sided geometric shapes and can serve as an innovative alternative media in mathematics learning at school.